Challenges and Opportunities in Fintech Adoption by Micro Enterprises: A Case Study of Magelang, Indonesia - Wahyu Agus Widadi; Nindya Farah Dwi Puspitasari (Publikasi Indonesia, 2024)
Technological advancements, particularly in the field of Financial Technology (Fintech), play a significant role in the sustainability of Micro, Small, and Medium Enterprises (MSMEs). This study aims to assess the level of Fintech utilization in MSME operations in Magelang Regency, with a focus on Micro Enterprises. The research employs a descriptive qualitative method, combining a literature review with interviews and observations of several MSME business actors. The findings reveal that while Fintech holds potential for supporting MSME growth, its adoption among micro-businesses in Magelang remains limited. Fintech is largely used as a supplementary tool rather than a core component of business operations. To fully maximize the utilization and benefits of Fintech in the Micro business sector, MSMEs require guidance and outreach programs on digital literacy and the practical application of Financial Technology. Additionally, infrastructure support, such as reliable internet connectivity, is essential to ensure access to information across various regions.